Prognostic factors and outcomes of adjuvant and first-line metastatic treatments in melanoma a Turkish oncology group study - Nargiz Majidova; Hacı Arak; Faruk Recep Ozalp; Onur Bas; Gulhan Ozcelik Koker; Erkan Buket Ozmarasalı; Yasemin Sagdıc Karateke; Teoman Sakalar; Sendag Yaslikaya; Ilknur Deliktas Onur; Goncagul Akdag; Ali Ogul; et al. (Scientific Reports)
Abstract Management of melanoma has changed significantly with the discovery of targeted therapies and immune checkpoint inhibitors (ICI). Our aim in the study is to determine which treatment alternatives, specifically dabrafenib plus trametinib and ICIs, are effective in adjuvant therapy and which treatment is effective as first-line metastatic therapy. This retrospective, multicenter study included 120 patients diagnosed with stage IIIB-IIID melanoma receiving both adjuvant and first-line metastatic treatment between 2007 and 2023. Data on clinicopathologic characteristics, treatment regimens and outcomes were collected. Objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS) and overall survival (OS) were analyzed. Patients treated with dabrafenib plus trametinib as adjuvant therapy had the longest relapse-free survival (RFS) (median: 8.3 months), followed by those treated with interferon (4.1 months) and nivolumab (1.9 months) (p = 0.002). Metastatically, the highest ORR was observed in patients treated with dabrafenib plus trametinib (54.5%), followed by ICI (52.0%) and chemotherapy (33.3%). Similarly, DCR was superior for dabrafenib plus trametinib (86.3%) compared to ICI (70.8%) and chemotherapy (66.6%). Median PFS was 9.7 months (95% CI 7.2–12.2 months) in the whole group. This was 14.3 months (95% CI 9.6–19.0 months) with ICI, 10.3 months (95% CI 4.2–16.4 months) with BRAF/MEK inhibitors and 6.3 months (95% CI 4.7–7.9 months) with chemotherapy, which was statistically significant (p < 0.001). Dabrafenib plus trametinib showed the longest median OS (53.5 months) in metastatic patients and was significantly better than chemotherapy (33.6 months) (p < 0.001). BRAF V600E mutation, RFS > 6 months, ORR are all independent factors for OS prognosis. In our study, dabrafenib plus trametinib combination was more effective in adjuvant treatment of melanoma, while immunotherapy was more effective in metastatic first-line treatment.